IMPLEMENTATION OF AUGMENTED REALITY AS A HAIR MODEL VISUALIZATION MEDIA BASED ON ANDROID - Fatahillah Aji Maulana; Suprianto Suprianto; Nuril Lutvi Azizah (Universitas Teknokrat Indonesia, 2023)
Humans place a high value on physical appearance. An attractive appearance can increase a person's self-confidence. Hairstyles are one of several ways to achieve an attractive appearance. This implies that there is always a demand for barbershops. However, some traditional barbershops, like Mr. Abdi, use outdated techniques like hanging flyers for haircut models that are no longer relevant in this era. This has an effect on the very low level of interest among young people who use services provided by roadside barbershops. The objective of this study is to create applications that have a way of delivering information that is interactive and different from other modern barbershops using augmented reality (AR), which will be used as a medium for visualizing hairstyles. In this study, the markerless tracking method is used to display three-dimensional objects in various types of fields. This application was developed with Unity and Vuforia because the development process can be done quickly. Based on the results, the overall quality of the software is 84%, so it is feasible for mass use.